Student dissatisfaction in Higher Education: a ‘fuzzy’ index approach - Steve Cook (Studies in Higher Education, 2024)
The revamp of the National Student Survey (NSS) has led to the elimination of the final ‘overall satisfaction’ question for Higher Education Institutions in England. This paper develops an index approach that can effectively summarise student satisfaction, utilising a ‘fuzzy poverty’ methodology that assigns weights to dissatisfaction outcomes based on their correlation levels. We show how our dissatisfaction index enables a comprehensive sector-level analysis by combining NSS data with sector-wide data and further show the usefulness by presenting a case study. Our approach can be universally and unbiasedly applied to student surveys globally, while alleviating problems related to the removal of the overall satisfaction question in the UK.